An estimation of the local growth rate from Cosmicflows peculiar velocities. Issue 1 (27th March 2019) - Dupuy, Alexandra; Courtois, Helene M; Kubik, Bogna
Abstract: This article explores three usual estimators, noted as v 12 of the pairwise velocity, ψ1 and ψ2 of the observed two-point galaxy peculiar velocity correlation functions. These estimators are tested on mock samples of Cosmicflows-3 data set (Tully, Courtois & Sorce), derived from a numerical cosmological simulation, and also on a number of constrained realizations of this data set. Observational measurements errors and cosmic variance are taken into consideration in the study. The result is a local measurement of f σ8  = 0.43(± 0.03)obs (± 0.11)cosmic out to z  = 0.05, in support of a ΛCDM cosmology.